Main Directions in Improving State Budget Policy - Yarmatov Sharofiddin Choriyevich, Ismatov Sharafiddin Asatulloyevich, Ortikov Shavkat Maxammadiyevich (International Journal of Advanced Science and Technology, 2020)
This article gives a brief explanation about the main directions of state budget policy and the importance of their implementation. In particular, trends in budget revenues and expenditures over the years are analyzed on the basis of statistics. The tax processes that play an important role in the state budget policy are compared with the tax processes of developed countries. The positive effects of medium-term budget projects on the budget process have been studied in the country. There are also suggestions for the proper implementation and development of budget policy in general.